A Decolonialidade e o feminismo decolonial revistos a partir das categorias PMEST de Ranganathan - Morais, Marilia Winkler de (Universidade Federal de São Carlos, 2022)
Decoloniality is a movement dedicated to continuous reflection on the Latin American cultural, political and social reality. The decolonial nature arises from the practices of opposition and intervention from the moment the first colonial subject reacted against the imperial purposes that began in the 15th century. In the academic project, decoloniality is expressed through the constitution of lines of thought, practices and authentic research in Latin America. Within the scope of decoloniality, the importance of decolonial feminism as a Latin American movement dedicated to gender and race issues in a perspective of resistance is highlighted. In view of this, the theories and methodologies of Knowledge Organization were used as emancipatory technologies as a basis for a better understanding of the conceptual arrangements on these phenomena. Thus, the general objective of this research is to establish a diagnosis and delimit a set of minimum and initial procedures for the construction of a conceptual semantic network that encompasses the narrative context of decoloniality, in order to enable its identification in the context of Information Science. Specifically, the objective is to analyze how much the so-called Fundamental Categories of Ranganathan (1967), namely: Personality, Matter, Energy, Space and Time, would allow to list a set of statements that make up the structure of decolonial narratives from notions that move of the usual denotative meanings, synthesized at the level of a conceptual map. To this end, an exploratory theoretical study was conducted based on bibliographic analysis on decoloniality and decolonial feminism. In order to structure the semantic network of terms and concepts that make up these narratives, the reasoning method of the categories Personality, Matter, Energy, Space and Time (PMEST) by Ranganathan (1967) was used, and they were expanded in the light of the suggested Literary Categories by Costa (2008). Among the results, it was found that the chosen procedures allowed a theoretical-conceptual approximation between these Categories and the elements that structure decolonial discourses, in addition to exposing how the relationship between their concepts is broad and permeated with essential connotative aspects that allow us to better understand the dimension of these themes. We conclude that studies like this are necessary so that decoloniality and decolonial feminism can achieve greater visibility and representation, becoming increasingly disciplinary content, lines of research and intervention projects, in addition to contributing to the strengthening of decolonial thinking as constitutive in Latin American Information Science.
Decoloniality and decolonial feminism reviewed from Ranganathan's PMEST categories
Keywords: Decolonialidade; Feminismo Decolonial; Shiyali Ramamrita Ranganathan; Rede Semântica; Mapa Conceitual; Ciência da Informação; Decoloniality; Decolonial Feminism; Semantic Network; Conceptual Map; Information Science; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO